2019
DOI: 10.1590/1984-0462/;2019;37;1;00007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Do Perfil Nutricional Em Pacientes Portadores De Fibrose Cística De Acordo Com Faixa Etária

Abstract: Most of the patients presented adequate nutritional status and adequate consumption of calories and macronutrients, indicating appropriate nutritional management. New studies focusing on preschool children should be performed to assess if it is possible to reduce the nutritional risk of patients with cystic fibrosis at older ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In the evaluation of the z score according to weight of the participants, the mean z score for children aged 2-10 was 0.1500 ± 1.18621, while the mean z score for children aged 11-18 was -1.4431 ± 1.33970 and there is no statistically significant difference between the two age groups (p=0.107).In a cross-sectional study of 101 children and adolescents with cystic fibrosis in Brazil, Neri et al reported adequate calorie and macronutrient consumption and adequate nutritional status in most patients. However, lower BMI z scores were observed in schoolchildren (5 to <10 years) and adolescents (≥10 years) (20). In another study, 76 children with CF in Greece, 9% of boys and 5% of girls were underweight (BMI Z score for age <-2.0) despite patients meeting or exceeding the recommended total energy intake (19).…”
Section: Discussionmentioning
confidence: 95%
“…In the evaluation of the z score according to weight of the participants, the mean z score for children aged 2-10 was 0.1500 ± 1.18621, while the mean z score for children aged 11-18 was -1.4431 ± 1.33970 and there is no statistically significant difference between the two age groups (p=0.107).In a cross-sectional study of 101 children and adolescents with cystic fibrosis in Brazil, Neri et al reported adequate calorie and macronutrient consumption and adequate nutritional status in most patients. However, lower BMI z scores were observed in schoolchildren (5 to <10 years) and adolescents (≥10 years) (20). In another study, 76 children with CF in Greece, 9% of boys and 5% of girls were underweight (BMI Z score for age <-2.0) despite patients meeting or exceeding the recommended total energy intake (19).…”
Section: Discussionmentioning
confidence: 95%
“…As demonstrated in a recent study, while infants were not underweight, in the preschool age group, around 10% had a nutritional profile below expectations, a proportion that increased significantly among students (35.3%) and adolescents (33.3%). 30 However, regarding BMI percentile and BMI-Z, the higher interquartile range observed in 2020 compared with 2018 deserves attention. The analysis of the absolute and relative frequencies of patients' distribution among each categorization of BMI percentile and BMI-Z showed more people with large gains but also with large losses in 2020 than in 2018, which eventually might have contributed to no significant change in the median.…”
Section: Discussionmentioning
confidence: 96%
“…It is crucial to recognize the early signs of abnormal glucose metabolism to diagnose CFRD. Early diagnosis and treatment correlate with slower rates of pulmonary decline and improved growth 38 …”
Section: Discussionmentioning
confidence: 99%